G35 National surveillance of severe microcephaly diagnosed in infants in the United Kingdom and Ireland. (25th October 2020) - Knowles, RL; Sampaio, M; Solebo, AL; Sargent, J; Oluonye, N; Rahi, JS
Abstract : Background: Severe microcephaly is defined by WHO as a head circumference (HC) more than 3 standard deviations below mean (<-3SD) for age and sex. Although UK congenital anomaly registrations suggest microcephaly is uncommon, there is uncertainty about the number of babies affected each year. To monitor emerging infections, such as Zika Virus, and understand the impact on health and neurodevelopment, it is essential to characterise the current burden of disease. Aim: To report the incidence, characteristics and causes of severe microcephaly diagnosed in children aged under one year in the UK and Ireland. Methods: Active surveillance through the British Paediatric Surveillance Unit for 13 months from October 2017 to ascertain all live born children aged under 1 year who were diagnosed during this period with microcephaly or noted to have a HC <-3SD or <0.4th percentile for age and sex, excluding babies with anencephaly. Clinicians who reported a child completed a clinical questionnaire. The annual incidence of severe microcephaly was calculated for infants with HC <-3SD for age and sex. For all other analyses, children with HC <0.4th percentile were also included. All reported findings are based on confirmed cases to date. Results: The annual incidence of severe microcephaly (HC <-3SD) between November 2017 and October 2018 was 5.6 cases per 100, 000 children aged under 1 year. Sixty-one children met the study case definition (51% girls; 41% born <37 weeks gestation; 56% white, 26% Asian, 18% other/unknown ethnicity). Neurodevelopmental abnormalities were reported for 46 (75%) children, including seizures, vision, hearing, and motor abnormalities. The most common identified causes of microcephaly were genetic conditions (n=5) and congenital infections (CMV, toxoplasmosis, and herpes; n=8), however the cause was unknown for 69% infants. No cases of Congenital Zika Syndrome were identified. Conclusions: The number of children with confirmed severe microcephaly was fewer than estimates based on European congenital anomaly registers. Infants of Asian ethnicity and those born preterm were over-represented. Most children were still under investigation for the cause of the microcephaly. Over three-quarters of children already demonstrated neurological abnormalities; further follow-up will capture later neurodevelopmental outcomes.